Exercise-Induced Muscle Damage Following a Bout of Sport Specific Repeated Sprints - Howatson, Glyn; Milak, Adi (Journal of strength and conditioning research, 2009)
Howatson, G and Milak, A. Exercise-induced muscle damage following a bout of sport specific repeated sprints. J Strength Cond Res 23(8)2419-2424, 2009-Exercise-induced muscle damage (EIMD) is a popular area of investigation; however, many of the existing methods to induce muscle damage lack specificity to a sporting context. The aim of this investigation was to examine the extent of damage precipitated from a sport-specific, repeated sprint protocol and therefore elucidate its suitability as an appropriate model to investigate EIMD. Twenty male subjects (age 22 ± 2 years, height 178 ± 6.6 cm, mass 84.6 ± 13.6 kg in mean ± SD) volunteered. Following a standardized warm-up, they conducted 15 × 30 m sprints with a 10-m deceleration zone in which subjects were required to come to a complete halt; each repetition was separated by 60 seconds of rest. Maximum isometric force (MVC), serum creatine kinase activity (CK), muscle soreness (DOMS), and limb girth were taken immediately before and at 24 hours, 48 hours, and 72 hours after exercise to elucidate the extent of muscle damage. There were significant time effects for all dependent variables. CK and DOMS were significantly elevated above baseline for 72 hours postexercise (p < 0.05), whereas MVC was significantly lower and limb girth remained significantly elevated for 48 hours postexercise (p < 0.05). These data show that the repeated sprint protocol with a rapid deceleration precipitates significant levels of damage in the days following the exercise bout and therefore may be used as a suitable alternative to examine the damage response from a sport specific repeated sprint mode of exercise.